Effectiveness of Ultraviolet-C Light and a High-Level Disinfection Cabinet for Decontamination of N95 Respirators - Jennifer L. Cadnum; Daniel Li; Sarah N. Redmond; Amrita R. John; Basya Pearlmutter; Curtis Donskey (Case Western Reserve University, 2020)
Background-Shortages of personal protective equipment (PPE) including N95 filtering facepiece respirators is an urgent concern in the setting of the global COVID-19 pandemic.  Decontamination of PPE could be useful to maintain adequate supplies, but there is uncertainty regarding the efficacy of decontamination technologies. Methods-A modification of the American Society for Testing and Materials standard quantitative carrier disk test method (ASTM E-2197-11) was used to examine the effectiveness of ultraviolet-C (UV-C) light, a high-level disinfection cabinet that generates aerosolized peracetic acid and hydrogen peroxide, and dry heat at 70°C for 30 minutes for decontamination of bacteriophages Phi6 and MS2 and methicillin-resistant Staphylococcus aureus (MRSA) inoculated onto 3 commercial N95 respirators.  Three and 6 log10 reductions on N95 respirators were considered effective for decontamination and disinfection, respectively.  Results-UV-C administered as a 1-minute cycle in a UV-C box or a 30-minute cycle by a room decontamination device reduced contamination but did not meet criteria for decontamination of the viruses from all sites for any of the N95s.  The high-level disinfection cabinet was effective for decontamination of all the organisms from the N95s and achieved disinfection with 3 disinfection cycles over ~60 minutes.  Dry heat at 70°C for 30 minutes was not effective for decontamination of the bacteriophages.   Conclusions-UV-C could be useful to reduce contamination on N95 respirators.  However, the UV-C technologies studied did not meet our criteria for decontamination under the test conditions used.  The high-level disinfection cabinet was effective for decontamination of N95s and met criteria for disinfection with multiple cycles.